PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN ATTRACTIVE DAN LONG LASTING GUNA MENINGKATKAN KOMPETENSI PEDAGOGIK GURU MGMP BAHASA INGGRIS MADRASAH TSANAWIAH SE-KABUPATEN MADIUN - Ambarwati, Rosita; Sari, Dwi Rosita (Jurnal Terapan Abdimas, 2016)
Workshops and seminars in the field of education has been widely implemented , but it is still rarely discussed in detail about creating instructional media . In addition , observations of teachers' competence of MGMP Madrasah Tsanawiah Kabupaten Madiun , it can be said that the competence of most teachers are still weak . Most teachers still have many obstacles in achieving the learning objectives. This condition as a background of this teachers' training on making attractive and long lasting media. The success of this program will be seen from (1) the existence of a positive change in attitude and a new understanding of teachers that English learning process can be more fun with the learning media ; (2) the emergence of understanding of the various media that attractive and long lasting in English subject ; and (3) the emergence of innovations in the application of learning media in the classroom